Genomics of chloroplasts and mitochondria - Knoop, Volker; Bock, Ralph (Advances in Photosynthesis and Respiration, Including Bioenergy and Related Processes, 2012)
The past decade has witnessed an explosion of our knowledge on the structure, coding capacity and evolution of the genomes of the two DNA-containing cell organelles in plants: chloroplasts (plastids) and mitochondria. Comparative genomics analyses have provided new insights into the origin of plastids and mitochondria by primary and higher-order endosymbioses and uncovered an enormous evolutionary dynamics of organellar genomes. In addition, these studies have greatly helped to clarify phylogenetic relationships, especially in algae and early land plants with limited morphological and anatomical diversity. This book, written by leading experts in plant organelle biology, summarizes our current knowledge about plastid and mitochondrial genomes in all major groups of algae and land plants. It also includes chapters on endosymbioses, plastid and mitochondrial mutants, RNA editing, horizontal gene transfer, gene expression profiling and methods for the genetic transformation of organellar genomes. The book is designed for graduate students and researchers in plant molecular biology, taxonomy, ecology, biotechnology as well as cell and evolutionary biology.